Self-induced transparency of focused light pulses - Palonpon, Almar F. (2000)
Self-induced transparency (SIT) of foucsed light pulse is studied using the method of angular spectrum of plane wave (ASPW). In this method, the pulse is decomposed into a spectrum of plane wave components where the propagation of each component wave determined using the plane wave theory of SIT. Our calibration results show that at low numerical apetures (NA <=0.5) of the focusing objective lens, ASPW is in exact agreement with Fraunhoffer's paraxial diffraction theory but differs at high numerical apertures (NA > 0.5). Application of ASPW in the propagation of focused light pulses in a reasonant absorber medium reveals that focusing enhances the transmission of SIT pulses. The transparent pulses have larger peak intensities and larger pulse widths than the unfocused case. Pulse parameters such as pulse width, peak intensity and pulse delay are found to depend on NA. High NA produces larger pulse width and larger pulse delay than low NA. Peak intensity decreases with an increase in NA. Temporal profiles also show that the focused light pulse has a slower speed than the solitary plane wave pulse.